Myofibroblasts in oral health and odontogenic lesions - Srikanth Ramarao Prabakar; T Dinesh Kumar; Rajkumar Krishnan; S Sunil Prakash (Wolters Kluwer Medknow Publications, 2016)
Myofibroblasts (MFs) are the cells that are not only essential for the integrity of the human body by virtue of its role in physiological tissue repair (wound healing), but can also threaten it by its ability to promote tumor development. Under physiological conditions, after wound healing, MFs disappear by apoptosis, but when there is continued insult, these MFs persist in the tissue and result in dysfunctional repair mechanisms causing excessive secretion of extracellular matrix with resultant fibrosis and scarring. MFs are phenotypically altered fibroblasts and are a unique group of smooth muscle-like fibroblasts that have a similar appearance and function regardless of their tissue of residence. MFs originate from different precursor cells, the major contribution being from local recruitment of connective tissue fibroblasts. However, local mesenchymal stem cells, bone marrow-derived mesenchymal stem cells, and cells derived from an epithelial-mesenchymal transition process, may represent alternative sources of MFs when local fibroblasts are not able to satisfy the requirement for these cells during repair. Apart from pathological remodeling of tissues, they play an important role in organogenesis and oncogenesis, inflammation, repair, and fibrosis. Because of their ubiquitous presence in all tissues, MFs play important roles in various organ diseases and perhaps in multisystem diseases as well. In the light of such severe consequences of MF appearance and dysfunction, the necessity of more profoundly understanding the molecular mechanisms of MF formation and function is essential. This article highlights the overview of MFs and their role in oral health and disease particularly in relation to odontogenic lesions.